2016
DOI: 10.1016/j.palaeo.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Palynostratigraphy and palynofacies of the early Eocene Gurha lignite mine, Rajasthan, India

Abstract: A 105 m early Eocene section exposed in the Gurha Mine in the Nagaur-Ganganagar Basin, Rajasthan, India, archiving remains of equatorial vegetation at a time of extreme global warmth and close to the onset of the India-Eurasia collision, is investigated using palynostratigraphic and palynofacies analyses. Four palynozones e.g., Palmidites plicatus Singh, Botryococcus braunii Kützing, Triangulorites bellus Kar and Ovoidites ligneoulus are identified stratigraphically on the basis of abundance of these pollen ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The characteristic pollen assemblages, Sastripollenites trilobatus (Venkatachala and Kar, 1969), Ratariacolporites plicatus (Kar, 1985), Clavaperiporites jacobii (Ramanujam, 1966), C. densus (Thanikaimoni et al, 1984), Triangulorites bellus (Kar, 1985), Dermatobrevicolporites exaltus (Kar, 1985), and Kielmeyerapollenites eocenicus (Sah and Kar, 1974), reported from the Palana Formation indicate an early Eocene (Ypresian) age (Shukla et al, 2014). A similar pollen assemblage is also known from the early Eocene Naredi Formation of the Kutch Basin (Kar and Saxena, 1981; Kar, 1985) and the Cambay Formation of the Cambay Basin (Kumar, 1996; Rao et al, 2013); a late Paleocene–early Eocene age was reported for the lignites and associated sediments of Rajasthan in general (Kar and Sharma, 2001).
Figure 1Location map of the Gurha opencast lignite mine, near Bikaner, western Rajasthan, India: ( 1 ) map of India showing location of Rajasthan; ( 2 ) map of Rajasthan, showing location of Bikaner district; ( 3 ) map of Bikaner district showing location of the Gurha opencast lignite mine.
Figure 2Stratigraphy and lithologies exposed in the Gurha opencast lignite mine, near Bikaner, western Rajasthan, India.
…”
Section: Geologic Settingsupporting
confidence: 60%
See 1 more Smart Citation
“…The characteristic pollen assemblages, Sastripollenites trilobatus (Venkatachala and Kar, 1969), Ratariacolporites plicatus (Kar, 1985), Clavaperiporites jacobii (Ramanujam, 1966), C. densus (Thanikaimoni et al, 1984), Triangulorites bellus (Kar, 1985), Dermatobrevicolporites exaltus (Kar, 1985), and Kielmeyerapollenites eocenicus (Sah and Kar, 1974), reported from the Palana Formation indicate an early Eocene (Ypresian) age (Shukla et al, 2014). A similar pollen assemblage is also known from the early Eocene Naredi Formation of the Kutch Basin (Kar and Saxena, 1981; Kar, 1985) and the Cambay Formation of the Cambay Basin (Kumar, 1996; Rao et al, 2013); a late Paleocene–early Eocene age was reported for the lignites and associated sediments of Rajasthan in general (Kar and Sharma, 2001).
Figure 1Location map of the Gurha opencast lignite mine, near Bikaner, western Rajasthan, India: ( 1 ) map of India showing location of Rajasthan; ( 2 ) map of Rajasthan, showing location of Bikaner district; ( 3 ) map of Bikaner district showing location of the Gurha opencast lignite mine.
Figure 2Stratigraphy and lithologies exposed in the Gurha opencast lignite mine, near Bikaner, western Rajasthan, India.
…”
Section: Geologic Settingsupporting
confidence: 60%
“…Similarly, the Gurha mean annual temperature is cooler than that of today (~27°C), and the modern mean annual range of temperature (2.8°C) is smaller (Shukla et al, 2014). Paleobotanical evidence points toward a near-coastal tropical flora of evergreen trees subject to frequent wildfires under a strongly seasonal precipitation (monsoon) regime (Kumar et al, 2016; Spicer et al, 2017). The analysis of Spicer et al (2017) showed that, at the time of deposition of the Gurha mine sediments, this part of the Indian continent was subject to a seasonal climate more akin to the present-day Intertropical Convergence Zone–influenced Indonesia-Australia Monsoon, rather than the Himalaya-influenced South Asia Monsoon experienced in the region today.…”
Section: Discussionmentioning
confidence: 99%
“…6, Table 3). The Gurha-72m Flora is early Eocene in age (Shukla et al, 2014;Kumar et al, 2016) and the Tirap Flora is late Oligocene (Srivastava et al, 2012). Both floras existed in coastal lowlands near sea-level as evidenced by laterally equivalent marine units.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This valuable tool has been used in palaeoenvironmental, palaeoclimatological and palaeoceanographic reconstructions (e.g. van der Zwan 1990, Tyson 1995, Batten 1996, Gastaldo et al 1998, Cirilli et al 2015, Hochuli et al 2015, García Muro et al 2016, Kumar et al 2016, Okeke & Umeji 2016, Koch et al 2017) and has recently been tested in characterization of Holocene alluvial and palustrine deposits (e.g. Gastaldo & Huc 1992, Laggoun-Défarge et al 1995, Cohen et al 1999, Di Giovanni et al 1999, Bourdon et al 2000, Sebag et al 2006a, b, Serna et al 2015 through the identification and quantification of organic matter (OM) phytoclasts according to their origin, nature, formation or preservation in sedimentary processes.…”
mentioning
confidence: 99%